Full random effects models (FREM): A practical usage guide - E. Niclas Jonsson; Joakim Nyberg (Wiley, 2024)
Abstract The full random‐effects model (FREM) is an innovative and relatively novel covariate modeling technique. It differs from other covariate modeling approaches in that it treats covariates as observations and captures their impact on model parameters using their covariances. These unique characteristics mean that FREM is insensitive to correlations between covariates and implicitly handles missing covariate data. In practice, this implies that covariates are less likely to be excluded from the modeling scope in light of the observed data. FREM has been shown to be a useful modeling method for small datasets, but its pre‐specification properties make it a very compelling modeling choice for late‐stage phases of drug development. The present tutorial aims to explain what FREM models are and how they can be used in practice.